Harbor porpoise Phocoena phocoena (Linnaeus, 1758) - Read, Andrew J.; Keener, William; Webber, Marc A.; Siebert, Ursula (Elsevier, 2025)
The harbor porpoise was described as Delphinus phocoena by Linnaeus in 1758 from “Oceano, Europaeo & Balthico” and assigned to the genus Phocoena by Cuvier in 1816. Hershkovitz (1966) provides numerous synonyms, and as noted by Schevill et al. (1969), both the genus and species names have been misspelled occasionally as “Phocaena phocaena” from the Latin spelling of porpoise, “phocaena.” There are nine junior synonyms: P. ventricosus, communis, tuberculifera, vomerina, brachycium, americana, rondeletti, lineata, and relicta (Jefferson, 2021).